A multi-criteria sustainability assessment and decision-making framework for DME synthesis via CO2 hydrogenation - Gao, Ruxing; Wang, Lei; Zhang, Leiyu; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng; Zhu, Yuezhao (Energy, 2023)
CO2-to-DME (CTD) technology has been considered as a worthy solution for waste CO2 upcycling and green DME production. Faced with various emerging CTD routes with pros and cons, it is important to systematically assess and compare their attractiveness and difference, and identify the most sustainable technologies for further development and improvement. Thus, the present study proposed four promising CTD routes (i.e., two-step routes using high- and medium-concentration methanol as intermediates, and one-step routes with and without RWGS reactions) and developed a multi-criteria sustainability assessment and decision-making framework for alternative routes comparison and prioritization. Eleven KPIs were considered from technical, economic, and environmental perspectives to evaluate system sustainability. Exergoeconomic and exergoenvironmental analysis were conducted to pinpoint the location, magnitude, and sources of system inefficiencies from the component level. A TOPSIS method was employed to integrate multidimensional performances and present an informed decision-making process. As a result, all the alternative routes are sustainable for DME synthesis, and therein the one-step route without RWGS reaction always ranks as the most competitive choice through rigorous sensitivity analysis. Moreover, this work provides a strategic decision support for assessing the trade-offs involved in existing and emerging sustainable CO2 upcycling technologies towards carbon neutrality.
Keywords: CO2-to-DME; Decision-making frameworks; Environmental analysis; Exergoeconomic analysis; Multi criteria decision-making; Multi-criteria; Multi-Criterion; Multicriteria decision-making; Multicriterion decision makings; Sustainability assessment; CO2-to-DME; Exergoeconomic and environmental analysis; Multi-criteria decision-making; Sustainability assessment